Pulsed high intensity laser versus low intensity laser on healing of full thickness wound in diabetic rats (histological and immunohistochemical study) - HESHAM GALAL MAHRAN,; EMAN MOHAMED FARUK,; NASER A. ELSAWY,; WARDAHABDULLAH MOHAMMED ALASMARI,; ABDULLAH GLILRADA ALKUSHI, (International Journal of Pharma and Bio Sciences, 2017)
To evaluate and compare the effects of pulsed high-intensity and low-intensity laser on wound healing in diabetic rats, which was represented by transforming in wound surface areas, rate of healing and immunohistochemical study of Desmin phenotype characteristics of myofibroblasts. One hundred and twenty mature male albino rats had been divided into two groups: (G1) was used like a control to study the conventional skin structure. (G2) had been intraperitoneal injected by streptozotocin (STZ) to provide diabetic rat model. After anesthesia, full thickness wounds (2×2. 5cm) were created in all rats’ nape, and then divided directly into 3 equal groups; Group A) received pulsed high-intensity laser (Nd: YAG laser light, 1064nm), Group B) received low intensity laser (GAlAs Laser, 830 nm) with 5 j/cm2 and overall energy equal to 25 joules using a scanning technique, 3times/week for 3 weeks for both laser techniques. Group C) (control +ve) received no treatment. Measurements of wounded area, rate of epithelialization, histological and immunohistochemical evaluation also were conducted. In both HILT group and LILT group, there were better significant reductions of WSA along with better epithelization rate than those in the control group, and there was clearly no significant difference between each laser's effect on wound recovery. Histological results revealed fast reepithelization of epidermal level with the increase in dermal thickness, which characterized by thick collagen bundles and cellular infiltrates in both laser treated groupings, and immunohistochemical examination showed an increase in the number of desmin-positive immunoreactivity compared with that in the control group. Both HILT and LILT lasers at intensity of 5j/cm2 have facilitating effect on wound healing inform of shrinkage of WSA with no significant difference between both effects at that intensity level.